Lived Experience of Married Middle-aged Women Regarding Marital Satisfaction - Johnson L.K.; Senthilkumar Thavasiappan; Nandini Mannadath; Adheena Mariya B.; Alphonsa Siby; Angela Robert; Jilna Jiji; Sreevidhya V.K. (International Journal of Women's Health Nursing And Practices, 2024)
Introduction: Marital satisfaction is a significant contributor to general sense of happiness. A fulfilling marital relationship meets the intimacy requirements of both partners and contributes to their overall physical and mental well-being. However, elderly couples in today's era face new challenges associated with prolonged longevity. A study was conducted to explore the lived experience of marital satisfaction among married middle-aged women in selected community in Kannur. Objective of study was to identify the lived experience of middle-aged women regarding marital satisfaction. Methods: The study employed a qualitative research approach with a phenomenological design. Purposive sampling was utilized to select participants, and in-depth interviews were conducted with 10 married women in middle age at their residences, using a semi-structured interview guide. Results: Sample characteristics were analyzed using descriptive statistics and qualitative data were analyzed using Colazzi's seven-stage method. Most of the subjects were in age groups of 25 to 34 and 45 to 54 years. In all, 70% subjects belong to Christian religion, 40% of them have secondary or higher secondary education, 40% had family income about less than INR 10000, 80% belongs to nuclear family, 60% of subjects lived in rural area of residence, most of subjects 90% had an arranged marriage, 40% of subjects use mass media such as newspapers and others, and 50% of subjects are homemakers. Themes and subthemes derived from qualitative analysis are physical dimension (sexual satisfaction, disturbance due to physical issues in marital life, problems with shared bedroom), social dimension (change in social life, effect of social media), financial satisfaction (satisfaction with family income, efficiency of spouse to manage family budget), spiritual dimensions (religious beliefs and support), psychological dimension (life before and after marriage, expectation before and after marriage, limitations in decision making among couples, fear in marital life, challenging part in marital life, thought about not getting married), behavioral dimension (fight and its cause in marital life, bad habits in marital life ), satisfaction with partner (shortcomings felt in partner, dependence upon the partner), and communication aspect in marital life (quality of communication, concept about non-disclosure of fact).
Keywords: Phenomenology; lived experience; marital satisfaction; middle-aged women